2000
DOI: 10.4049/jimmunol.164.4.2160
|View full text |Cite
|
Sign up to set email alerts
|

Engagement of the OX-40 Receptor In Vivo Enhances Antitumor Immunity

Abstract: The OX-40 receptor (OX-40R), a member of the TNFR family, is primarily expressed on activated CD4+ T lymphocytes. Engagement of the OX-40R, with either OX-40 ligand (OX-40L) or an Ab agonist, delivers a strong costimulatory signal to effector T cells. OX-40R+ T cells isolated from inflammatory lesions in the CNS of animals with experimental autoimmune encephalomyelitis are the cells that respond to autoantigen (myelin basic protein) in vivo. We identified OX-40R+ T cells within primary tumors and tumor-invaded… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
290
1
1

Year Published

2002
2002
2017
2017

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 358 publications
(301 citation statements)
references
References 49 publications
(63 reference statements)
8
290
1
1
Order By: Relevance
“…Anti-CD40 mAb increased OT-I cells to a similar level. In contrast, three other mAb, anti-CTLA-4, anti-CD25 and anti-OX40, which have all shown therapeutic activity in tumour settings [19][20][21], boosted OT-I cells only modestly (Table 1), with anti-CTLA-4 mAb being the most active with around 2% OT-I cells at the peak response. It is important to note that the anti-CD25 mAb (PC61) was shown to deplete CD25 1 cells when assessed with a second non-blocking anti-CD25 mAb.…”
Section: Resultsmentioning
confidence: 99%
“…Anti-CD40 mAb increased OT-I cells to a similar level. In contrast, three other mAb, anti-CTLA-4, anti-CD25 and anti-OX40, which have all shown therapeutic activity in tumour settings [19][20][21], boosted OT-I cells only modestly (Table 1), with anti-CTLA-4 mAb being the most active with around 2% OT-I cells at the peak response. It is important to note that the anti-CD25 mAb (PC61) was shown to deplete CD25 1 cells when assessed with a second non-blocking anti-CD25 mAb.…”
Section: Resultsmentioning
confidence: 99%
“…Signaling via OX40 can reverse an already established state of tolerance even after the onset of antigen-specific hypo-responsiveness suggesting that OX40 represents an appropriate target for therapeutic intervention in a variety of diseases (Bansal-Pakala et al 2001), however the role of OX40R/OX40L interaction in the immune response to malignancies has only recently been recognised. OX40R over-expression was reported in tumour infiltrating lymphocytes and tumour-draining lymph node cells from melanoma, breast cancer, colon cancer and head and neck cancer patients, and their presence suggested a correlation with overall survival rate (Vetto etal, 1997;Weinberg et al, 2000, Petty et al, 2002. Unlike its involvement in autoimmunity where reduced clinical signs induced by blocking the OX40R-OX40L interaction or depletion of CD4 + cells, the anti-tumour adjuvant properties of the OX40 is based on it's engagement with its ligand during the initiation process of active immunisation, which leads to enhanced cytokine production and increased numbers of antigen-specific memory cells (Weinberg, 2002).…”
Section: Discussionmentioning
confidence: 99%
“…OX40/OX40L binding engages in the activation of effector T cells and impairs suppressive function of T reg . 53,54 Hence, it is reasonable that an OX40 agonist is responsible for tumor regression via restoring the ability of CD8 þ T cells. 55,56 A phase I study performed in melanoma patients with anti-OX40 mouse monoclonal antibody confirmed its potent antitumor property.…”
Section: Combination Strategiesmentioning
confidence: 99%